2005
DOI: 10.1007/s00066-005-1372-0
|View full text |Cite
|
Sign up to set email alerts
|

Individual Radiosensitivity Does not Correlate with Radiation-Induced Apoptosis in Lymphoblastoid Cell Lines or CD3+ Lymphocytes

Abstract: Only a subgroup of hypersensitive patients may be identified by reduction of radiation-induced apoptotic rate. It is concluded that the hypothesis according to which hypersensitive cells have reduced levels of apoptosis is only conditionally true. The authors suggest that this assay can be used in combination with additional tests evaluating DNA double-strand break repair, cell-cycle control and chromosomal aberrations for the evaluation for individual hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…A decrease in levels of radiation induced apoptosis with increasing age was reported in studies investigating CD3, CD4 and CD8 lymphocytes (Wistop et al, 2005;Ozsahin et al 1997). The data from these studies agreed with the data found in this study.…”
Section: Discussionsupporting
confidence: 91%
“…A decrease in levels of radiation induced apoptosis with increasing age was reported in studies investigating CD3, CD4 and CD8 lymphocytes (Wistop et al, 2005;Ozsahin et al 1997). The data from these studies agreed with the data found in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Loss of clonogenicity could be due to differentiation, senescence, and, predominantly in lymphocytes and lymphoblastoid cell lines, the induction of apoptosis [38]. Probably, diverse events lead to the reduced amounts of cells in G2/M.…”
Section: Discussionmentioning
confidence: 99%
“…When the G0 assay is used, the observed chromosomal aberrations are the consequence of either insufficient DNA repair [5,24,30,31,33], aberrant signal transduction for cell-cycle control, inappropriate activation of cell death as through apoptosis, differentiation, or senescence [29,35,38]. One major mechanism which prevents cells to undergo permanent DNA damage is the induction of a cell-cycle arrest, giving cells time to repair DNA damage and to avoid an unintentional progression through the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…After up to 72 h of incubation in standard conditions, the cells were fixed for 15 min in 4% paraformaldehyde and visualized using a fluorescence-microscope (Zeiss, Axioplan, Oberkochen, Germany) with a suitable filter combination (Fluorescein/Texas Red) at a 600x magnification. The data was analyzed with the Biomas image analyzing software (Erlangen, Germany) [18]. The values are given as grey values per nucleus [10,11,19,20] after incubation with DOX and DOX-TRF.…”
Section: Fluorescence Measurements Of the Free Drug And Dox-trf Distrmentioning
confidence: 99%
“…At least 1,000 cells per slide were counted blind with a fluorescence-microscope (Zeiss, Axioplan, Oberkochen, Germany) with a suitable filter combination (Fluorescein/Texas Red) at a 400x magnification. The data was analyzed with Biomas (Erlangen, Germany) [18]. The results are given as percentages (apoptotic cells/total cells x 100).…”
Section: Fluorescence Measurements Of the Free Drug And Dox-trf Distrmentioning
confidence: 99%